2018
DOI: 10.1039/c7rp00137a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of math SAT on women's chemistry competency beliefs

Abstract: In chemistry, lack of academic preparation and math ability have been offered as explanations as to why women seem to enroll, perform, and graduate at lower levels than men. In this paper, we explore the alternative possibility that the gender gap in chemistry instead originates from differential gender effects of academic factors on students’ motivation. Using a sample of approximately 670 students enrolled in a mid-sized university in the United States we conducted: (1)t-tests to understand incoming academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 52 publications
4
48
0
Order By: Relevance
“…For example, the number of mathematics courses taken in high school is a strong independent predictor of students' college achievements in introductory science courses [49]. Likewise, research suggests that high school math grades and SAT math scores can predict college physics course success [50][51][52]. In one study, high school preparation in math was found to be the strongest predictor of students' physics grades in college [8].…”
Section: B Self-efficacy Gender and Performance In Physicsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the number of mathematics courses taken in high school is a strong independent predictor of students' college achievements in introductory science courses [49]. Likewise, research suggests that high school math grades and SAT math scores can predict college physics course success [50][51][52]. In one study, high school preparation in math was found to be the strongest predictor of students' physics grades in college [8].…”
Section: B Self-efficacy Gender and Performance In Physicsmentioning
confidence: 98%
“…In our model, we use the Scholastic Assessment Test (SAT) math scores as a predictor variable, which ranged from 400 to 800 and is designed to predict first-year university performance. Prior research suggests that students may overgeneralize the implications of their performance on the SAT, believing that lower math SAT scores imply lower ability for physical sciences [52].…”
Section: Pre-college Test Scoresmentioning
confidence: 99%
“…In the case of postsecondary chemistry, self-concept holds predictive ability over performance when controlling for other known success predictors such as SAT math scores (Lewis et al, 2009). The relationship from previous achievement to subsequent measures of self-concept is also supported through empirical studies (e.g., Doran & Sellers, 1978;Helmke & van Aken, 1995;Vincent-Ruz, Binning, Schunn, & Grabowski, 2018). Research at the elementary level has established support for the reciprocal influence of self-concept and achievement in the general context (Guay, Marsh, & Boivin, 2003) and the math context (Marsh, Trautwein, Lüdtke, Köller, & Baumert, 2005) along with other measures, such as math anxiety (Ahmed, Minnaert, Kuyper, & van der Werf, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Reports on the Scholastic Aptitude Test (SAT) have shown that performance differences across the test vary by gender, with a large score advantage to men in the math section, a large advantage to women in the writing section, and relatively small differences in the verbal section (Mattern, Camara, & Kobrin, ). Students may internalize the scores they receive on the SAT as fundamental statements about aptitude in (or out of) science (Vincent‐Ruz, Binning, Schunn, & Grabowski, ). Alternatively, these aptitude estimates could be predictors of course performance, which then drives beliefs about disciplinary aptitude.…”
Section: Theoretical Frameworkmentioning
confidence: 99%